STUDENTS’ PERCEPTION ON THE USE OF MIND MAPPING TECHNIQUE TO IMPROVE STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT - Anisa Pitriyani Pitri (Universitas Jambi, 2022)
The objective of the research is to explore the students’ perception of using Mind Mapping in writing descriptive text. Also, this study aims to describe the advantages and disadvantages of using Mind Mapping in writing descriptive text. This research used mix-method design, in which the data were collected through questionnaire and interview. The participants of this study were the students of SMA Negeri 1 Muara Bungo and also interviewed an English teacher. The data obtained from interviews were analyzed. There were three major points, first students’ interest in using mind mapping in writing descriptive, second the difficulty in using mind mapping for students, third improve students’ writing skills. According to the data, mind mapping had a positive impact on students’ writing skills i.e. students’ better understanding and know what they are doing. In conclusion students think that mind mapping is interesting, and have advantages and disadvantages. The implication of this research is to increase students awareness in using mind mapping for writing.